The Methodology of Laboratory Markets and Its Implications for Agency Research in Accounting and Auditing - Dejong, Douglas V.; Forsythe, Robert; Uecker, Wilfred C. (Journal of Accounting Research, 1985)
Agency problem, Laboratory experiments, Negligence liability rule, Strict liability rule